A novel CeO.sub.2/MgAl.sub.2O.sub.4 composite coating for the protection of AZ31 magnesium alloys - Peng, Guangchun; Qiao, Qianqian; Jin, Lei; Zhang, Bowei; Wang, Yi; Huang, Kang; Yao, Qiong (Journal of materials science, 2020)
A novel CeO.sub.2/MgAl.sub.2O.sub.4 composite coating, fabricated via a cathode plasma electrolytic deposition (CPED) technique followed by hydrothermal synthesis, was developed in this study to explore its potential application as corrosion protection for AZ31 magnesium alloys. The microstructure observed through scanning electron microscopy indicated that reducing the duty cycle of the power source within a reasonable range during the CPED process was beneficial to form a uniform and dense MgAl.sub.2O.sub.4 coating, which served as an ideal adhesive matrix for a uniform CeO.sub.2 coating as the outermost layer. The results of electrochemical impedance spectra and neutral salt spray tests showed that the decoration of the CeO.sub.2 layer significantly improved the corrosion resistance of the CeO.sub.2/MgAl.sub.2O.sub.4 composite coating compared to the single MgAl.sub.2O.sub.4 coating and bare substrate. Cross-cut tests revealed that the adhesion of the MgAl.sub.2O.sub.4 coating and the CeO.sub.2/MgAl.sub.2O.sub.4 composite coating were both excellent due to the strong binding between the MgAl.sub.2O.sub.4 coating and the substrate.